Laser-Plasma Acceleration. - Ferroni, F. (IOS Press, 2012)
Impressive progress has been made in the field of laser-plasma acceleration in the last decade, with outstanding achievements from both experimental and theoretical viewpoints. Closely exploiting the development of ultra-intense, ultrashort pulse lasers, laser-plasma acceleration has developed rapidly, achieving accelerating gradients of the order of tens of GeV/m, and making the prospect of miniature accelerators a more realistic possibility. This book presents the lectures delivered at the Enrico Fermi International School of Physics and summer school: ""Laser-Plasma Acceleration"", held in.